2012
DOI: 10.1002/da.21994
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Dimensional Anxiety Scales for DSM-v in an Unselected Sample of German Treatment Seeking Patients

Abstract: The application of the dimensional anxiety scales may be an effective way to screen for specific anxiety disorders and to supplement categorical diagnoses in DSM-V, although further evaluation and refinement of the scales (particularly the specific phobia scale) is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 28 publications
12
81
0
Order By: Relevance
“… It should be noted that the use of Cronbach's alpha to assess internal consistency is limited and that a more rigorous statistical approach to assessing the unidimensionality of the scales is confirmatory factor analyses (CFAs). A separate manuscript (Beesdo‐Baum et al , ) utilizing these methods confirmed the findings of the present study.…”
supporting
confidence: 88%
“… It should be noted that the use of Cronbach's alpha to assess internal consistency is limited and that a more rigorous statistical approach to assessing the unidimensionality of the scales is confirmatory factor analyses (CFAs). A separate manuscript (Beesdo‐Baum et al , ) utilizing these methods confirmed the findings of the present study.…”
supporting
confidence: 88%
“…DSM-5 Dimensional Anxiety Scales (DSM-5 DAS) [3941] is a brief screening questionnaire designed to provide both dimensional assessment of anxiety symptoms, as well as a threshold score (14) identifying clinically significant anxiety [41]. …”
Section: Methodsmentioning
confidence: 99%
“…In our study, one factor with an eigenvalue over 1 was obtained. The eigenfactor value of the first factor was 6.602 and it explained 66.0% of total variance and was in congruity with the original construct of the scale (12).…”
Section: Discussionmentioning
confidence: 70%